Antenatal diagnosis of cardio-facio-cutaneous syndrome: Prenatal characteristics and contribution of fetal facial dysmorphic signs in utero. About a case and review of literature. (September 2019) - Biard, Jean-Marc; Steenhaut, Patricia; Bernard, Pierre; Race, Valérie; Sznajer, Yves
Abstract: Antenatal diagnosis of cardio-facio-cutaneous syndrome: prenatal characteristics and contribution of fetal facial dysmorphic signs in utero. This paper is a case study and review of literature. "RASopathies" is the term coined for a group of genetic diseases that share modulation inside the MAPKinase pathway. Mutations inside the coding sequence of any of these genes may be responsible for the upregulation of the RAS pathway, leading on the clinical level to Type 1 Neurofibromatosis (NF1), Noonan syndrome (NS), Costello syndrome (CS), Multiple Lentigines, Loose Anagen Hair syndrome, Cardio-Facio-Cutaneous syndrome (CFCS), and, more recently, Legius syndrome. While the postnatal presentation of this group is well-known, prenatal findings are less well recognized. The presence of a RASopathy during the prenatal period can be suspected on account of non-specific abnormalities: polyhydramnios, cystic hygroma or high nuchal translucency, macrosomia with proportionate short long bones, macrocephaly, renal, lymphatic, or cardiac defects. The current case report underlines the characteristic dysmorphic facial features on 3D-ultrasound (hypertelorism, down-slanting palpebral fissures, a long and marked philtrum, and low-set posteriorly rotated ears) that allow for a "RASopathy" to be postulated. After detecting a copy number variation (CNV) absence on a CGH array, we performed a RASopathy gene panel analysis, which identified a so-far unreported heterozygous de novo mutation in the BRAF gene (namely NM_004333.4 : c.1396 G > C ; p.Gly466Arg). Genetic counseling has, therefore, focused on the diagnosis of a RASopathy and predictable phenotype of CFCS, a distinct entity characterized by an increased risk of intellectual disability and early-onset feeding problems. We suggest that a more detailed prenatal facial evaluation should be performed in fetuses presenting high nuchal thickness, heart defects, or unusual findings, along with the absence of a CNV on a CGH array. Due to the dysmorphic facial features, targeted RASopathy genes are presumed to likely to be responsible for NS, CFCS, and CS.